The prevalence of functional gastrointestinal disorders in children in Panama: a school-based study - Lu, Peter L.; Saps, Miguel; Chanis, Ricardo A.; Velasco-Benítez, Carlos A. (Acta Paediatrica, 2016)
Aim Functional gastrointestinal disorders (FGIDs) are common in children, but the epidemiology of FGIDs is incompletely understood. Our aim was to perform a population‐based study using Rome III criteria to describe the prevalence of FGIDs in children in Panama. Methods We performed a cross‐sectional study of children attending three schools in Panama City, Panama. Children with organic medical diseases were excluded. Subjects provided demographic information and completed the Questionnaire on Pediatric Gastrointestinal Symptoms – Rome III Spanish version. Results A total of 321 subjects (61.1% female, median age 10 years, range 8–14 years) completed our study. A total of 92 subjects (28.7%) met criteria for an FGID. Gender, age and school type did not differ significantly between subjects with and without FGIDs. The most common FGIDs included functional constipation (15.9%), irritable bowel syndrome (5.6%), and functional abdominal pain or functional abdominal pain syndrome (4.0%). Abdominal pain‐related FGIDs were present in 12.1%. Conclusion FGIDs are common in school‐aged children in Panama. The prevalence of abdominal pain‐related FGIDs in children in Panama is similar to that described in other parts of the world. Further population‐based studies utilising Rome III criteria to measure FGID prevalence in children are needed to advance our understanding of the pathogenesis of FGIDs.